Iowa Birdline update, January 16, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for January 16, 1989. There are no new good sightings this week but several of the birds sighted in recent weeks can still be found. Epson - sheet feed/flatbed